2015
DOI: 10.1111/asj.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forages on the chemical compositions and antiosteoporotic activities of velvet antlers

Abstract: For this study, we aimed to assess the dose-response antiosteoporotic effects of the middle section of velvet antlers (VAs) from sika deers (Cervus nippon) fed with different types of fodders. VAs prepared from farmed sika deers fed with feed mixtures containing sorghum distillery residue (VA-SDR) or without SDR (SDR replaced with hay, VA-Hay) were divided into upper (VAU), middle (VAM) and basal (VAB) sections. The chemical constituents of the middle sections obtained from each VA type were compared, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies (Ren et al, 2019 ; Tseng et al, 2016 ) have found that sika deer antler protein extract can obviously alleviate osteoporosis. In order to further study the mechanism of treating osteoporosis, the mechanism of its action on osteoporosis was clarified by studying the changes of serum biochemical indexes, micro‐CT scanning, and intestinal flora in osteoporosis model mice.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies (Ren et al, 2019 ; Tseng et al, 2016 ) have found that sika deer antler protein extract can obviously alleviate osteoporosis. In order to further study the mechanism of treating osteoporosis, the mechanism of its action on osteoporosis was clarified by studying the changes of serum biochemical indexes, micro‐CT scanning, and intestinal flora in osteoporosis model mice.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that velvet antler is rich in amino acids, the content is as high as about 50%, there are at least 17 types, and it contains protein, phospholipids, cholesterol, sphingomyelin, and ganglioside, ceramides, polyamines, chondroitin sulfate A, estrone, estradiol, prostaglandins PGE1, PGE2, etc. and 20 kinds of trace elements such as calcium, phosphorus, magnesium, and copper (Tseng et al 2016 ). Velvet Antler Peptide (VAP) isolated from velvet antler.…”
Section: Introductionmentioning
confidence: 99%
“…Sika deer antler is a precious traditional Chinese medicine, which widely used in China to treat various kidney diseases, it has many pharmacological activities such as anti‐oxidation, tissue repair, anti‐osteoporosis and treatment of bone resorption diseases (Cheng, Jian, Chen, & Liu, ; Kim, Bak, Jo, & Cheong, ; Tseng, Chen, Lai, Wang, & Wang, ). The study found that its active ingredients mainly include inorganic elements, amino acids, lipids, proteins, peptides, sugars, vitamins, hormones, nucleic acids, base components, etc.…”
Section: Introductionmentioning
confidence: 99%